Pelatihan Pemandu Wisata bagi Penggiat Wisata di Desa Wonosari Kecamatan Sepaku Kabupaten Panajam Paser Utara - Yeni Santi; Nurlaeli Nurlaeli; Rahmatiyah Rahmatiyah; Agus Prasetyo; Ernayanti Nur Widhi; Rusna Ristasa (Lembaga Pengembangan Kinerja Dosen, 2025)
The tour guide training is conducted as part of the Community Service program by lecturers from Universitas Terbuka Daerah Samarinda in collaboration with the National Capital Authority (IKN). This training is a key component to enhance the quality of tourism services in Wonosari Village, Sepaku District, Panajam Paser Utara Regency, which has excellent tourism potential and a strategic location as a pillar of IKN development. The main goal of this training is to strengthen the capacity and skills of participants in providing professional and high-standard tourism services. The tour guide training is attended by 25 young tourism enthusiasts from Wonosari Village and surrounding areas. They receive training materials and conduct practical guiding activities, accompanied by trained instructors over a three-day period. Through this training, it is expected to create a satisfying tourism experience for visitors, which in turn will encourage sustainable tourism development in the village.